Effect of inclusion rate of silage with or without alpha-amylase trait on finishing steer growth performance, carcass characteristics, and agronomic efficiency measures - Rusche, Warren C (Transl Anim Sci, 2020)
One hundred ninety-two Continental × British steers [initial body weight (BW) = 420 kg (standard deviation = 24.7)] were used in a randomized complete block design finishing study to evaluate the effects of feeding two types of silage germplasm at two inclusion rates. A 2 × 2 factorial arrangement of treatments was used with either a conventional hybrid (Golden Harvest G07B39-311A, Syngenta Seeds LLC, Minnetonka, MN; CON) or a hybrid with increased expression of alpha-amylase (Syngenta Enogen Feed corn, Golden Harvest E107B3-3011A-EVT5, Syngenta Seeds, LLC; ENO) fed at either 12% (12SIL) or 24% (24SIL) of diet dry matter. Steers were blocked by source and location (source 1: first three pen replicates, n = 10 steers per pen with a fourth pen replicate of six steers per pen; source 2: one pen replicate, n = 12 steers per pen) and assigned randomly within block to treatments, resulting in five pens and 48 steers per treatment. Steers were harvested after 126 (12SIL) or 140 (24SIL) days on feed (DOF). There were no silage hybrid by inclusion rate interactions detected for live growth performance (P ≥ 0.15). Silage hybrid did not affect average daily gain (ADG), gain-to-feed ratio (G:F), or final BW (FBW; P ≥ 0.35). Feeding 24% silage reduced ADG (P = 0.04) and increased G:F (P = 0.01) but increased FBW (P = 0.02) because of greater DOF compared with 12SIL. A hybrid by inclusion rate interaction was detected (P = 0.04) for calculated yield grade (YG) with steers fed 24SIL having increased YG within CON but not ENO. Hot carcass weight and rib fat were unaffected by silage hybrid (P ≥ 0.81) but were increased by feeding 24SIL (P = 0.03 and P = 0.02, respectively). Feeding increased amounts of silage increased beef produced per hectare (P = 0.05). Source of silage did not affect feedlot growth performance of cattle but, because of slight differences in estimated silage yield, conventional silage produced more kilograms of beef per hectare (P < 0.01). Feeding increased amounts of silage reduced G:F on both a live and carcass-adjusted basis but increased kilograms of beef produced per unit of land, which is paramount to cattle feeders who grow their own feedstuffs.